The Construction of Merida’s Self-Determination in Pixar’s Brave (2012): A Characterization Study - M.Ques Al Qoroni; Novi Sriwulandari; M.Ainul Yaqin (Indonesian Journal of Multidisciplinary on Social and Technology, 2026)
This study examines the construction of Merida’s self-determination in Pixar’s Brave (2012) through characterization analysis. The film presents Merida as a young princess who struggles to define her own path amid family expectations, royal tradition, and social pressure. Her character is significant because her conflict is not only about rejecting an arranged marriage, but also about the human need to be heard, respected, and allowed to choose one’s own life direction. This study aims to explain how self-determination is represented through Merida’s dialogue, actions, and relationships with other characters. The research uses a qualitative descriptive method and applies Abrams and Harpham’s theory of characterization, especially the distinction between showing and telling. The data are taken from selected scenes and dialogues that reveal Merida’s inner conflict, independence, and emotional growth. The findings show that Merida’s self-determination is built through her direct speech, rebellious actions, and changing relationship with Queen Elinor. The study concludes that Brave portrays self-determination as a human process involving freedom, responsibility, misunderstanding, and reconciliation.